Resuscitative Strategies in Traumatic Hemorrhagic Shock - Supandji, Mia; Budipratama, Dhany; Pradian, Erwin (Perdatin Pusat, 2015)
Trauma and brain injury are common in young patients with a high incidence of mortality. The classic triadof death in a trauma involves hypothermia, acidosis and coagulopathy. This physiologic derangement plays animportant role in exsanguination and death of trauma patients, if it is not promptly diagnosed and aggressivelytreated. However, the optimal strategy is still debatable. Damage Control Resuscitation along with damage controlsurgery has been proven to increase patients survival. DCR is a management of patients with trauma startedfrom the emergency room up to the operating room and the intensive care unit (ICU). Five pillars of DCR are 1.Body rewarming, 2. Correction of acidosis, 3. Permissive hypotension, 4. Restrictive luids administration and 5.Hemostatic resuscitation. Early and aggressive transfusion of blood and blood products, with comparison of PRC,FFP and platelets of 1:1:1, if no whole blood available, can improve the outcome and survival of the patients.